2020
DOI: 10.1038/s41598-020-59721-w
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Trocar Site Hernia after Laparoscopic Cholecystectomy

Abstract: Trocar site hernia (TSH) is an incisional hernia occurring at the trocar insertion sites after different types of laparoscopic surgeries. the aim of this study is to present characteristics of patient and surgery series with trocar site hernia after laparoscopic cholecystectomy. A 2930 consecutive patients underwent laparoscopic cholecystectomy in two major university-affiliated hospitals from April 2014 to March 2018 and the patient followed up for variable periods of time. Retrospective medical chart review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 22 publications
(11 reference statements)
5
19
1
6
Order By: Relevance
“…7,14 -15 Trocar-site hernia is associated with obesity, duration of surgery, age, diabetes mellitus, incision enlargement, and wound infection; thus, proper fascial closure is even more essential in patients with those risk factors. 16 In the current study, the mean closure time of EZ-Close TM was 87.9 Ϯ 21.0 s. This result is comparable to that of previously published studies evaluating conventional suturing devices. According to an in vitro study in cadaver models, the mean closure time of the conventional Carter-Thomason system was 133.6 Ϯ 54.6 s. 17 Another study reported that the Carter-Thomason needle technique took an average of 8 min to close two 10-mm port sites, although the time of complete skin closure was counted.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…7,14 -15 Trocar-site hernia is associated with obesity, duration of surgery, age, diabetes mellitus, incision enlargement, and wound infection; thus, proper fascial closure is even more essential in patients with those risk factors. 16 In the current study, the mean closure time of EZ-Close TM was 87.9 Ϯ 21.0 s. This result is comparable to that of previously published studies evaluating conventional suturing devices. According to an in vitro study in cadaver models, the mean closure time of the conventional Carter-Thomason system was 133.6 Ϯ 54.6 s. 17 Another study reported that the Carter-Thomason needle technique took an average of 8 min to close two 10-mm port sites, although the time of complete skin closure was counted.…”
Section: Discussionsupporting
confidence: 87%
“… 7 , 14 – 15 Trocar-site hernia is associated with obesity, duration of surgery, age, diabetes mellitus, incision enlargement, and wound infection; thus, proper fascial closure is even more essential in patients with those risk factors. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Patient factors associated with herniation include older age and elevated body mass index with increased intra-abdominal pressure and reduced fascial strength suggested as contributory factors. Although diabetes mellitus has been suggested as a potential risk factor, there is little evidence regarding the impact of patient comorbidity on hernia development [ 6 , 7 ]. Technical factors, which may affect the incidence of trocar-site hernia, include trocar size and position, fascial closure and procedure duration.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the decision was made to perform a laparoscopic mesh-based repair approach for accurate measurement of the hernial defect size and reduce the risk of surgical site infection. It is also well known that trocar-site hernia was associated with obesity, wound infection, and the use of > 10-mm trocar [14]. Compared with the open access technique, direct trocar insertion was considered superior in terms of port-site hernia, infection, and pain [7,15].…”
Section: Discussionmentioning
confidence: 99%